A clinical algorithm to determine target blood pressure in the elderly: evidence and limitations from a clinical perspective - Jinho Shin; Kwang-il Kim (Clinical Hypertension, 2022)
Abstract As the elderly population is growing rapidly, management of hypertension in South Korea faces major challenges because the proportion of elderly hypertension patients is also increasing. The characteristics of this population are also much more complex than younger patients. Elderly hypertension is characterized by wide variations in (1) fitness or biological age, (2) white-coat effect, (3) poor functional status or frailty, (4) dependency in activities of daily living or institutionalization, (5) orthostatic hypotension, and (6) multiple comorbidities. All of these should be considered when choosing optimal target blood pressure in individual patients. Recent randomized clinical trials have shown that the benefits of intensive blood pressure control for elderly patients is greater than previously thought. For generalization of these results and implementation of the guidelines based on these studies, defining the clinician’s role for individualization is critically important. For individualized decisions for target blood pressure (BP) in the elderly with hypertension, four components should first be checked. These consist of (1) the minimum requirement of functional status and capability of activities of daily living, (2) lack of harmful evidence by the target BP, (3) absence of white-coat hypertension, and (4) standing systolic BP ≥ 110 mmHg without orthostatic symptoms. Risk of decreased organ perfusion by arterial stenosis should be screened before starting intensive BP control. When the target BP differs among comorbidities, the lowest target BP should be given preference. After starting intensive BP lowering therapy, tolerability should be monitored, and the titration should be based on the mean level of blood pressure by office supplemented by out-of-office BPs. Applications of the clinical algorithms will be useful to achieve more standardized and simplified applications of target BP in the elderly.